Analisis Kualitas Pelayanan Di Puskesmas Menteng Kecamatan Jekan Raya Kota Palangka Raya - Simson Oktelhanan Lukius; Rionaldo Rionaldo; Andi Saputra; Rio Febrian (Professional: Jurnal Komunikasi dan Administrasi Publik, 2026)
Health service quality is an important factor in determining the level of community satisfaction with health facilities, especially public health centers (Puskesmas) as primary healthcare providers. This study aims to analyze the quality of services at the Menteng Health Center, Jekan Raya District, Palangka Raya City based on service quality dimensions. The research method used is descriptive qualitative with a literature study approach using relevant scientific journals. The results show that the service quality at Menteng Health Center is generally categorized as good, but several aspects still need improvement, especially in service time and procedures. The dimensions of tangibles, reliability, responsiveness, assurance, and empathy contribute to patient satisfaction, although there are still gaps between expectations and actual services. The conclusion is that the service quality at Menteng Health Center is fairly good but not yet optimal, so improvements are needed in service speed, ease of procedures, and facilities to increase community satisfaction.